An ellipse in polar coordinates

Calculus Level 3

The polar coordinates description of an ellipse is given by:

r ( θ ) = 1 5 + 3 cos θ + 2 sin θ r(\theta) = \dfrac{1}{5 + 3 \cos \theta + 2 \sin \theta}

Find the sum of its semi-major and semi-minor axes lengths.

Inspiration


The answer is 0.7053.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Joseph Newton
Sep 13, 2020

Let A cos ( θ + ϕ ) = 3 cos θ + 2 sin θ A\cos(\theta+\phi)=3\cos\theta+2\sin\theta . Expanding and solving gives A = 13 A=\sqrt{13} and ϕ = arccos 3 13 \phi=-\arccos\frac3{\sqrt{13}} , so r = 1 5 + 13 cos ( θ ϕ ) r=\frac1{5+\sqrt{13}\cos\left(\theta-\phi\right)} Let's rotate the entire ellipse by removing ϕ \phi to simplify this equation. This does not affect the shape of the ellipse. r = 1 5 + 13 cos ( θ ) r=\frac1{5+\sqrt{13}\cos(\theta)} 5 r + 13 r cos ( θ ) = 1 5r+\sqrt{13}r\cos(\theta)=1 25 r 2 = ( 1 13 r cos ( θ ) ) 2 25r^2=\left(1-\sqrt{13}r\cos(\theta)\right)^2 Now we convert to Cartesian coordinates with r 2 = x 2 + y 2 r^2=x^2+y^2 and r cos θ = x r\cos\theta=x 25 x 2 + 25 y 2 = ( 1 13 x ) 2 25x^2+25y^2=\left(1-\sqrt{13}x\right)^2 Expanding and completing the square for the x x terms gives 12 ( x + 13 12 ) 2 + 25 y 2 = 25 12 12\left(x+\frac{\sqrt{13}}{12}\right)^2+25y^2=\frac{25}{12} Let's translate the entire ellipse in the x x direction by removing 13 12 \frac{\sqrt{13}}{12} . This does not affect the shape of the ellipse. 12 x 2 + 25 y 2 = 25 12 12x^2+25y^2=\frac{25}{12} 144 25 x 2 + 12 y 2 = 1 \frac{144}{25}x^2+12y^2=1 This is the equation of an ellipse with semi-major axis 25 144 = 5 12 \sqrt{\frac{25}{144}}=\frac5{12} and semi-minor axis 1 12 \frac1{\sqrt{12}} , so the answer is 5 12 + 1 12 0.7053 \frac5{12}+\frac1{\sqrt{12}}\approx0.7053

Mark Hennings
Sep 13, 2020

Since r = 1 5 + 13 cos ( θ + α ) r = \frac{1}{5 + \sqrt{13}\cos(\theta + \alpha)} for some angle α \alpha , we see that 1 12 ( 5 13 ) = ( 5 + 13 ) 1 r ( 5 13 ) 1 = 1 12 ( 5 + 13 ) \tfrac1{12}(5-\sqrt{13}) = (5 +\sqrt{13})^{-1} \le r \le (5 - \sqrt{13})^{-1} = \tfrac{1}{12}(5 + \sqrt{13}) . Since the maximum and minimum distances from the focus of an elliptical orbit are a ( 1 + e ) a(1+e) and a ( 1 e ) a(1-e) , we deduce that a = 5 12 a = \tfrac{5}{12} and a e = 1 12 13 ae = \tfrac{1}{12}\sqrt{13} . Thus e = 13 5 e = \tfrac{\sqrt{13}}{5} and hence b = 1 12 b = \tfrac1{\sqrt{12}} , so a + b = 1 12 ( 5 + 12 ) = 0.7053418013 a+b=\tfrac{1}{12}(5 + \sqrt{12}) = \boxed{0.7053418013} .

Polar equation of an ellipse is

r ( θ ) = l 1 + e cos θ r(\theta) =\dfrac {l}{1+e\cos \theta} ,

where l = b 2 a = l=\dfrac {b^2}{a}= semi latus rectum,

e = 1 b 2 a 2 = e=\sqrt {1-\frac{b^2}{a^2}}= eccentricity,

a , b a, b are the semi-major and the semi-minor axes of the ellipse respectively.

Here

r ( θ ) = 1 5 + 3 cos θ + 2 sin θ r(\theta) =\dfrac {1}{5+3\cos \theta+2\sin \theta}

= 1 5 1 + 13 5 cos ( θ tan 1 2 3 ) =\dfrac {\frac 15}{1+\frac{\sqrt {13}}{5}\cos (\theta-\tan^{-1} \frac 23)}

So, l = b 2 a = 1 5 l=\dfrac {b^2}{a}=\dfrac 15 ,

e = 1 b 2 a 2 = 13 5 e=\sqrt {1-\frac{b^2}{a^2}}=\dfrac {\sqrt {13}}{5}

Solving we get a = 5 12 a=\dfrac {5}{12} ,

b = 1 12 b=\dfrac {1}{\sqrt {12}} , and

a + b = 5 + 12 12 a+b=\dfrac {5+\sqrt {12}}{12}\approx

7053418 \boxed {7053418}

Hosam Hajjir
Sep 13, 2020

We're given that,

r = 1 a + b cos θ + c sin θ r = \dfrac{1}{a + b \cos \theta + c \sin \theta}

From the definition of polar coordinates, we have the polar-to-rectangular coordinates relation

x = r cos θ , y = r sin θ ( 1 ) x = r \cos \theta, y = r \sin \theta \hspace{20pt} (1) .

First, we'll eliminate having to deal with three constants a, b, c , by combining b cos θ b \cos \theta and c sin θ c \sin \theta into one θ \theta -shifted sinusoid. If ϕ = Arctan2 ( b , c ) \phi = \text{Arctan2}( b , c ) , then,

r = 1 a + b cos ( θ ϕ ) r = \dfrac{1}{a + b' \cos(\theta - \phi) }

where b = b 2 + c 2 b' = \sqrt{ b^2 + c^2 } . Rotating our x x -axis to θ = ϕ \theta = \phi , the equation becomes,

r = 1 a + b cos θ ( 2 ) r = \dfrac{1}{ a + b' \cos \theta } \hspace{20pt} (2)

In the following, we will replace b b' with b b , for simplicity of notation.

Using ( 1 ) (1) and ( 2 ) (2) , we get,

x ( a + b cos θ ) = cos θ ( 3.1 ) x (a + b \cos \theta ) = \cos \theta \hspace{20pt} (3.1)

y ( a + b cos θ ) = sin θ ( 3.2 ) y (a + b \cos \theta ) = \sin \theta \hspace{20pt} (3.2)

Equations ( 3 ) (3) are a linear system in cos θ \cos \theta and sin θ \sin \theta , and if we define

u = [ cos θ sin θ ] u = \begin{bmatrix} \cos \theta \\ \sin \theta \end{bmatrix}

then, this linear system can be written as A u = B A u = B , where

A = [ ( x b 1 ) 0 y b 1 ] A = \begin{bmatrix} (x b - 1) && 0 \\ y b && -1 \end{bmatrix}

and

B = [ x a y a ] B = \begin{bmatrix} - xa \\ -y a \end{bmatrix}

Solving, we get,

cos θ = a x 1 b x \cos \theta = \dfrac{ ax }{1 - b x } and sin θ = a y 1 b x \sin \theta = \dfrac{ a y }{1 - b x}

Now since cos 2 θ + sin 2 θ = 1 \cos^2 \theta + \sin^2 \theta = 1 , then,

( a x ) 2 + ( a y ) 2 = ( 1 b x ) 2 (a x)^2 + (a y)^2 = (1 - b x )^2

a 2 ( x 2 + y 2 ) = 1 + b 2 x 2 2 b x \rightarrow a^2 ( x^2 + y^2 ) = 1 + b^2 x^2 - 2 b x

( a 2 b 2 ) x 2 + a 2 y 2 2 b x = 1 \rightarrow (a^2 - b^2) x^2 + a^2 y^2 - 2 b x = 1

Completing the square in x x , we obtain,

( a 2 b 2 ) ( x b a 2 b 2 ) 2 + a 2 y = 1 + b 2 a 2 b 2 = a 2 a 2 b 2 (a^2 - b^2) (x - \dfrac{b}{a^2 - b^2} )^2 + a^2 y = 1 + \dfrac{b^2}{a^2 - b^2} = \dfrac{a^2}{a^2 - b^2}

Dividing by the right hand side,

( a 2 b 2 ) 2 a 2 ( x x 0 ) 2 + ( a 2 b 2 ) y 2 = 1 ( 4 ) \dfrac{(a^2 - b^2)^2}{a^2} (x - x_0)^2 + (a^2 - b^2) y^2 = 1 \hspace{20pt} (4)

where x 0 = b a 2 b 2 x_0 = \dfrac{b}{a^2 - b^2}

From equation (4) , it is evident that the semi-major axis is given by a a 2 b 2 \dfrac{a}{a^2 - b^2} and the semi-minor axis is given by 1 a 2 b 2 \dfrac{1}{\sqrt{a^2 - b^2}} .

In this problem a = 5 , b = 3 , c = 2 a = 5 , b = 3 , c = 2 , so our b = 13 b' = \sqrt{13} which we replaced with b b .

Hence the semi-major axis = 5 25 13 = 5 12 = \dfrac{5}{25 - 13} = \dfrac{5}{12} , and the semi-minor axis is 1 12 \dfrac{1}{\sqrt{12}} . Their sum comes to 0.7053 \approx 0.7053 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...